Integration of graphene/ZnS nanowire film hybrids based photodetector arrays for high-performance image sensors. (9th June 2017) - Wu, Congjun; Wang, Fei; Cai, Caoyuan; Xu, Zhihao; Ma, Yang; Huang, Fan; Jia, Feixiang; Wang, Min
Abstract: High-performance photodetector arrays are desired to achieve integrated devices for various technological applications. Film based photodetectors have shown great potential as photodetector arrays because they are compatible with traditional complementary metal oxide semiconductor (CMOS) electronics. Herein, high-mobility graphene/single-crystal ZnS nanowire film hybrids based photodetector arrays have been successfully achieved. With 3 orders of magnitude higher conductance compared with ZnS nanoparticle films, single-crystal ZnS nanowire films are expected to enable a larger portion of photo-generated carriers to move to graphene channel via charge transfer mechanism. As a result, the as-produced graphene/ZnS nanowire film hybrids based devices possess a high photocurrent of 320 µ A, a high responsivity of 2.6 × 10 6 A W −1, a high detectivity of 8.0 × 10 12 Jones, and a low detectable light intensity of 1 µ W cm −2 . Moreover, the integrated graphene/ZnS nanowire film hybrids based photodetector arrays are demonstrated as high-performance image sensors with good uniformity.